Exome sequencing reveals mutations in MFN2 and GDAP1 in severe Charcot–Marie–Tooth disease. Issue 3 (September 2014) - Kostera‐Pruszczyk, Anna; Kosinska, Joanna; Pollak, Agnieszka; Stawinski, Piotr; Walczak, Anna; Wasilewska, Krystyna; Potulska‐Chromik, Anna; Szczudlik, Piotr; Kaminska, Anna; Ploski, Rafal
Abstract The aim of our study was to characterize electrophysiologically and explain the genetic cause of severe Charcot–Marie–Tooth (CMT) in a 3.5‐year‐old with asymptomatic parents and a maternal grandfather with a history of mild adult‐onset axonal neuropathy. Severity of neuropathy was assessed by Charcot–Marie–Tooth neuropathy score (CMTNS). Whole‐exome sequencing was performed using an Illumina TruSeq Exome Enrichment Kit on the HiSeq 1500 with results followed up by Sanger sequencing on an ABI Prism 3500XL (Applied Biosystems, Foster City, CA, USA). Paternity was confirmed using a panel of 15 hypervariable markers. Electrophysiological studies demonstrated severe axonal sensory‐motor neuropathy in the proband, mild motor neuropathy in his mother, and mild sensory‐motor neuropathy in his grandfather. CMTNS in the proband, his mother, and grandfather was 21, 1, and 12, respectively. On genetic analysis, the boy was found to carry a heterozygous dominant MFN2 T236M mutation transmitted via the maternal line and a de novo GDAP1 H123R mutation. Our findings emphasize the need to search for more than one causative mutation when significant intrafamilial variability of CMT phenotype occurs and underline the role of whole‐exome sequencing in the diagnosis of compound forms of CMT disease.